Impacts of phytoplankton availability on bigeye tuna (Thunnus obesus) recruitment in the Indian Ocean - Wang, Yang; Zhang, Yuying; Geng, Zhe; Zhu, Jiangfeng (Frontiers in Marine Science, 2024)
Introduction A sustainable fishery relies on consistent and substantial recruitment. There is, however, considerably high mortality among fish larvae during their early development. One of the most important factors determining larval survival is foraging success. Bigeye tuna is among the most important commercial species in the Indian Ocean. Despite being routinely researched and assessed, it remains unclear how food availability affects the recruitment success of bigeye tuna. Methods In this study, we used phytoplankton size (MD50) as an indicator of prey availability and investigated the connection between MD50 and bigeye tuna recruitment from 2000 to 2018 through the Beverton-Holt stock-recruitment function. The Indian Ocean was divided into four regions to accommodate spatial differences. Results As a result, larger MD50 could bring higher recruitment, particularly in the eastern and southern Indian Ocean. Based on the analysis, we inferred that for bigeye tuna, the eastern Indian Ocean is the primary spawning ground, and the peak spawning period falls in Season 2 (April-June). Discussion The conclusions provide valuable insights for understanding the recruitment characteristics of bigeye tuna in the Indian Ocean.